2021
DOI: 10.3390/antibiotics10080946
|View full text |Cite
|
Sign up to set email alerts
|

Successful Intratracheal Treatment of Phage and Antibiotic Combination Therapy of a Multi-Drug Resistant Pseudomonas aeruginosa Murine Model

Abstract: Background: Pseudomonas aeruginosa (PsA) is a common etiology of bacteria-mediated lower respiratory tract infections, including pneumonia, hospital acquired pneumonia (HAP), and ventilator-associated pneumonia (VAP). Given the paucity of novel antibiotics in our foreseeable pipeline, developing novel non-antibiotic antimicrobial therapies saliently targeting drug resistant PsA isolates remains a priority. Lytic bacteriophages (or phages) have come under scrutiny as a potential antimicrobial for refractory bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…In the context of lung infections with MDR-bacteria, phage therapy is of great interest for treating VAP patients. While recent studies used intratracheal applications [ 74 ] or nebulized phage suspensions [ 7 , 75 , 76 ], here we show that systemic applications of two different phage cocktails are suitable for the dissemination of phages to the lung. The phage cocktails are well-tolerated and do not induce a marked immune response in naïve mice warranting their future evaluation as antibacterial therapeutics.…”
Section: Discussionmentioning
confidence: 56%
“…In the context of lung infections with MDR-bacteria, phage therapy is of great interest for treating VAP patients. While recent studies used intratracheal applications [ 74 ] or nebulized phage suspensions [ 7 , 75 , 76 ], here we show that systemic applications of two different phage cocktails are suitable for the dissemination of phages to the lung. The phage cocktails are well-tolerated and do not induce a marked immune response in naïve mice warranting their future evaluation as antibacterial therapeutics.…”
Section: Discussionmentioning
confidence: 56%
“…While extant antibiotics and phages have unique antimicrobial effects individually, using them in combination is a promising option for persistent infections [ 50 , 51 , 52 ]. The goal of phage–antibiotic synergy (PAS) is to use a combination of a phage and an antibiotic to create a synergistic action against pathogenic bacteria, thereby evading or minimizing the development of bacterial resistance.…”
Section: Introductionmentioning
confidence: 99%
“…The goal of phage–antibiotic synergy (PAS) is to use a combination of a phage and an antibiotic to create a synergistic action against pathogenic bacteria, thereby evading or minimizing the development of bacterial resistance. For example, Duplessis showed that when merged with a sub-efficacious dose of meropenem, a combination of phages reduced the bacterial burden of an antibiotic-resistant strain of PsA and decreased mortality in a murine pneumonia model [ 52 ].…”
Section: Introductionmentioning
confidence: 99%
“…This model was chosen because it has been well characterized to mimic human disease, with bacterial proliferation in the lungs, acute inflammation, and development of pneumonia ( 10 12 ). Using this model, we have successfully evaluated the efficacy of numerous therapies either as monotherapy or as combination therapy with a representative carbapenem antibiotic, namely, meropenem ( 10 , 13 , 14 ). However, this model has limitations, including characterization with only one strain of P. aeruginosa and a lack of robust comparative antibiotics to gauge the success of novel INDs.…”
Section: Introductionmentioning
confidence: 99%